2023
DOI: 10.1177/00938548231164966
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Knowledge, Support, and Behavior Surrounding the Implementation of the Prison Rape Elimination Act

Abstract: The Prison Rape Elimination Act (PREA) was designed to eliminate from corrections systems all acts of sexual violence. PREA’s success will be determined by whether corrections staff and incarcerated persons support this law, understand its legal elements, and are enforcing it according to it’s original intentions. To date, few studies have examined whether members of both populations do indeed support PREA, and whether they are enforcing it correctly. To explore these issues, questionnaire data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…To mitigate this issue, the use of clearly written policies at suitable reading levels could minimize the need for interpretation and enhance compliance. Similarly, Smith et al (2023) identify the need to effectively communicate PREA policy, noting a lack of awareness could contribute to increased rates of unreported victimizations and improper enforcement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To mitigate this issue, the use of clearly written policies at suitable reading levels could minimize the need for interpretation and enhance compliance. Similarly, Smith et al (2023) identify the need to effectively communicate PREA policy, noting a lack of awareness could contribute to increased rates of unreported victimizations and improper enforcement.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing staff survey data across six institutions, Rudes et al (2021, p. 242) determined correctional staff did not perceive PREA as beneficial, and instead viewed its implementation as an "administrative, safety, and cultural burden." Similarly, Smith et al (2023), in their examination of staff and inmate perceptions and knowledge regarding PREA, emphasized successful implementation relied on the support and understanding of staff and inmates, noting if "either does not comprehend accurately this policy and/or express little to no support for it, this can severely hamper efforts to abolish acts of sexual harassment and/or assault within corrections" (p. 6). Survey data from staff and inmates revealed that while most staff and inmates had knowledge about and support for PREA, there were notable discrepancies in certain areas including mandatory reporting procedures and staff/inmate relationships.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This date range was selected to reflect an increased academic interest in boundary violations following legislative change in US prisons. The (Smith, 2008;Schuhmann and Wodahl, 2011). PREA's zero-tolerance policy brought visibility to the issue of prisoner-on-prisoner rape but also renewed calls to understand the nature of staff-on-prisoner sexual assaults and other boundary violative behaviours.…”
Section: Selection Criteriamentioning
confidence: 99%
“…PREA applies a zero-tolerance stance toward all forms of sexual misconduct occurring in the correctional system. To achieve its goal of completely eradicating sexual victimization, incarcerated persons (IPs) and correctional staff must hold favorable views of this law, and adopt behaviors that align with its central aims (Smith et al, 2023).…”
mentioning
confidence: 99%